SINCERE BEHAVIOR MODERATES THE RELATIONSHIP BETWEEN RECRUITMENT AND WORK SYSTEMS TOWARDS THE PERFORMANCE OF EMPLOYEE - Faryd Mardiansyah Lasman; Maskuri Sutomo; Niluh Putu Evvy Rossanty (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2023)
This study aims to analyze the relationship between recruitment and work systems on the performance of outsourced employees at the Representative Office of Bank Indonesia of Central Sulawesi Province by using the moderating variable of sincere behavior. This research was a quantitative type. This study used outsourced employees at the Representative Office of Bank Indonesia, Central Sulawesi Province, totaling 70 people as a population, all as samples. SEM PLS was used as an analytical tool, and google forms as a medium for collecting data. The results of this study indicate that (1) The recruitment system has a positive and significant effect on the performance of outsourced employees of the Representative Office of Bank Indonesia of Central Sulawesi Province (2) The work system has a positive but insignificant effect on the performance of outsourced employees of the Representative Office of Bank Indonesia of Central Sulawesi Province (3) Sincere behavior has a positive and significant effect as moderating the relationship between recruitment system and performance of outsourced employees of the Representative Office of Bank Indonesia of Central Sulawesi Province (4) Sincere behavior has a positive and significant effect as moderating the relationship between work system and performance of outsourced employees of the Representative Office of Bank Indonesia of Central Sulawesi Province.